Rzeczywistość i fikcja w mitach samorządności i egalitaryzmu Hiszpanii nowożytnej w kreowaniu współczesnych tożsamości narodowych - Pérez, Francisco José Alfaro (Studia Europaea Gnesnensia, 2015)
The article analyzes the ease with which issues related to the identity of a given social group can be created or committed to oblivion. Also, it examines the subjective and partial exploitation of historical facts which stems from ignorance or vested interests. The author presents a range of examples, covering the period from the rule of the old order (ancien regime) to the present day.